CLUSTERING THE HAPPINESS LEVEL OF PROVINCES IN INDONESIA USING K-MEANS - Heti Mulyani; Ricak Agus Setiawan (Journal of Information Technology and Its Utilization, 2024)
Community welfare is a government goal related to the fulfillment of basic needs, education and employment, which can be measured through the happiness index. The purpose of this research is to cluster provinces in Indonesia based on their resident’s happiness level. The data obtained from the Indonesian Central Bureau of Statistics website. The method used in this research is K-means clustering. There are 2 dimensions used, namely the personal dimension which includes education, employment, household income, health, housing conditions and, assets. The social dimension includes social relations, environmental conditions, security conditions, family harmony, and availability of free time. Based on the results of the study, 2 provincial groups were obtained based on the level of happiness. Testing is done using the Davies Bouldin Index (DBI). The optimal K is obtained, namely K = 2 with a DBI value of = 0.776. The first group is the happiest group including the provinces of North Maluku, Maluku, North Sulawesi, North Kalimantan, Gorontalo, Central Sulawesi, West Papua, Riau Islands, East Kalimantan. The other provinces are in the second group. The unhappiest groups are Banten, Bengkulu and Papua.